Myrmecophagous mammals in a changing world: the ecology of aardvarks and temminck’s pangolins in the kalahari - Phakoago, Makabudi valery (University of the Witwatersrand, Johannesburg, 2024)
Little is known about the distribution and ecology of the aardvark (Orycteropus afer) and Temminck’s pangolin (Smutsia temminckii) in southern Africa as they are rarely seen and difficult to study. Both species are myrmecophagous (feed on ants and termites), primarily nocturnal, 2and they tend to be solitary. Climate change, which is resulting in hotter and drier environments in most parts of southern Africa, may affect the aardvark and Temminck’s pangolin through direct impacts on the animals and through impacts on their prey resources. Understanding how climate change may impact these two myrmecophagous mammals requires us to gather further insights on how their environment and food sources are changing, how their diets overlap, how they use the environment and alter their activity to source food and buffer themselves from heat and cold, and how they are distributed across southern Africa. Previous research conducted in the semi-arid Kalahari of southern Africa showed that a decline in ant and termite populations (as indicated by counts in pitfall traps) associated with drought resulted in starvation of aardvarks and pangolins and decreased reproductive output of pangolins. Individuals of both species starved, despite previous work indicating that the diets do not overlap, with aardvark preying predominantly on harvester termites (Hodotermes mossambicus) and pangolins preying predominantly on ants (mainly Crematogaster ants). However, the research on each species was conducted at different times, so the dietary differences may have arisen from various factors that differed between the study periods. As part of a long-term project aimed at assessing the potential impacts of climate change on myrmecophagous mammals in the Kalahari ecosystem, the present study collected faecal samples from aardvark and Temminck’s pangolin at the same time in the Kalahari for one year to compare their diets and assess dietary overlap (Chapter 3). In addition to dietary analysis, the study added to our long-term data (since September 2014) of grass cover and counts of ants and termites in pitfall traps, from September 2019 to August 2022 (Chapter 2). These long-term data revealed substantial fluctuations in grass and insect availability over time, with termite populations apparently less likely to recover after drought years compared to ants (Chapter 2). The study also assessed the abundance xiii and orientation of burrows that are available to the aardvark and Temminck’s pangolin in the duneveld in the Kalahari during winter of 2021 (Chapter 4). Lastly, the study assessed the distribution and ecology of the aardvark and Temminck’s pangolin in southern Africa using freely available images and videos from Facebook and Instagram over 10 years (2010 – 2019) (Chapter 5). During the study, the study site, Tswalu Kalahari Reserve, experienced higher than average rainfall (2020 and 2021), resulting in high grass cover and an increase in the number of ants in pitfall traps, following a very hot and dry period in 2019. In contrast, termite numbers remained low. Despite the apparent low number of termites, as reflected in the pitfall traps, aardvark preferred termites over ants in their diet, and consumed predominantly termites of the genus Trinervitermes (45% of their diet) over the study period. Temminck’s pangolin preferred ants over termites and consumed mainly ants of the genus Crematogaster (42%). Although aardvarks and Temminck’s pangolin had preferences for their specific prey items, it was shown for the first time that there was dietary overlap between the two mammal species, with higher overlap when prey resources were readily available during autumn, and lower dietary overlap when prey resources were scarce during spring. The present study, however, was conducted during an unusually wet period characterized by above-average rainfall, so it is important to determine how competition for dietary items will change in hotter and drier years, when insect populations will likely be lower. Ants and termites rely on grasses for their survival; therefore, one would predict that the abundance of burrows, dug primarily by aardvark, is likely to be related to grass cover. The present study site comprised two distinct areas, differing in grass cover as a result of differences in historical grazing pressure. I therefore investigated the availability and use of burrows in the area with low grass cover and the area with high grass cover, during winter. Burrows serve as a beneficial buffer against climatic conditions for burrowing species, offering heat avoidance during the day and warmth during the night. It was found that burrow numbers were positively associated with grass cover. More burrows also were found on the western side of the dunes than on the eastern side, most likely because the xiv western side receives more direct sunlight in the afternoon, providing a warmer microclimate overnight during the cold winter. Finally, the study explored whether social media could provide supplementary information on the distribution and ecology of the aardvark and Temminck’s pangolin in southern Africa. The data, which were collected through examining photos and videos on Facebook and Instagram, confirmed that the aardvark is found throughout South Africa while Temminck’s pangolin is restricted to the northern regions of South Africa. The images also confirmed recent research that poor body condition is associated with greater diurnal activity for the aardvark, likely a response to high energetic demands of being active on cold nights. Little is known about drinking behaviour by the aardvark and Temminck’s pangolin, with only 7 records previously published for the aardvark. It was found a further 32 records for the aardvark, and 7 for the pangolin, showing that both species do occasionally drink opportunistically. The records also provided information on the predation of both myrmecophagous mammals. Predation was observed at almost all times of the year for both species, with leopard (Panthera pardus) the most common predator for the aardvark, and lion (Panthera leo) the most common predator for Temminck’s pangolin. Even though there were far fewer records of images in other southern African countries, social media appears to be a useful tool for collecting data on the distribution and ecology of the aardvark and Temminck’s pangolin. Understanding the ecology and distribution of the aardvark and Temminck’s pangolin in the Kalahari and other regions in relation to available prey resources and local climate is crucial for improving our conservation efforts of the species through informed management practices.
A research report submitted in fulfillment of the requirements for the Doctor of Philosophy, in the Faculty of Health Sciences, School of Physiology, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; myrmecophagous mammals; ecology of aardvarks; temminck’s pangolins; SDG-3: Good health and well-being